Sensitization to nsLTP: A Retrospective Study in An Italian Pediatric Population over the Last Decade - Cristiana Indolfi; Giulio Dinardo; Angela Klain; Marcella Contieri; Giuseppina Rosaria Umano; Fabio Decimo; Salvatore Abbadessa; Carolina Vitulano; Giorgio Ciprandi; Michele Miraglia del Giudice (Journal of Immunology Research)
Background. Food allergy is common in the Mediterranean, especially concerning lipid transfer proteins (LTPs) allergy. LTPs are widespread plant food allergens in fruits, vegetables, nuts, pollen, and latex. Also, LTPs are prevalent food allergens in the Mediterranean area. They can sensitize via the gastrointestinal tract and cause a wide range of conditions: from mild reactions, such as oral allergy syndrome, to severe reactions, such as anaphylaxis. LTP allergy in the adult population is well described in the literature, concerning both the prevalence and clinical characteristics. However, there is poor knowledge about its prevalence and clinical manifestation in children living in the Mediterranean. Materials and Methods. This study, including 800 children aged from 1 to 18 years, investigated the prevalence of 8 different molecules of nonspecific LTP over time in an Italian pediatric population visited over the last 11 years. Results. About 52% of the test population was sensitized to at least one LTP molecule. For all the LTPs analyzed, sensitization increased over time. In particular, using the years 2010 through 2020 as a comparison, the major increases were observed for the LTPs of the English walnut Jug r 3, the peanut Ara h 9, and the plane tree Pla a 3 (about 50%); the increase of the LTP of the Hazelnut Cor a 8 was about 36%, and that of the LTP of the artemisia Art v 3 was approximately 30%. Conclusions. The latest evidence in the literature indicates an increase in food allergy prevalence in the general population, including children. Therefore, the present survey represents an interesting perspective about the pediatric population of the Mediterranean area, exploring the trend of LTP allergy.